COVID-19 and Breakthrough infection among Physicians in a Tertiary Care Hospital of Dhaka, Bangladesh (Sir Salimullah Medical College Journal, 2026)
Background: Vaccination against SARS-CoV-2 is one of the major preventive ways of COVID-19 despite of that people become infected with SARS-CoV-2 after vaccination. The objective of this study was to observe the infection rate and Ct values of N and ORF 1ab gene of COVID 19 and breakthrough cases among physicians. Methods: A cross-sectional observational study was conducted at Department of Virology of SSMC, Dhaka, Bangladesh. A total of 64 vaccinated physicians of 4th wave (June- July 2022) for breakthrough cases and all the unvaccinated physicians (265) who tested for SARS CoV-2 in our laboratory during the same period of 1st wave (June- July 2020) were studied. Results: The percentage of breakthrough cases among vaccinated physicians was 46.9% (30); whereas the infection rate of COVID-19 among unvaccinated physicians was 18.5% (49).Majority of the (66.7%) breakthrough cases were female (20), while 65.3% of COVID-19 cases were male (32).A low mean Ct value for N genes was observed among breakthrough cases (24.8 ± SD 4.8) than the unvaccinated cases (27.8 ±SD 7.7). Among the breakthrough cases only 8.0 % of physicians became infected within 3 months, 63.0 % between 3-6 months and 29.0 % after 6 months of receiving last vaccine dose. Highest infection rate was observed during 1st (26.9%) and 3rd (22.6%) quarter of June for 1st and 4th wave of COVID-19 pandemic respectively. Conclusion: Higher percentage of breakthrough cases emphasizes that compliance with standard precaution along with vaccination is essential for the prevention of COVID-19.Sir Salimullah Med Coll J 2025; 33: 61-66